ANALYSIS OF AMMONIAC (NH3) AND HYDROGEN SULFIDE (H2S) IN AMBIENT AIR AROUND THE CIPEUCANG LANDFILL - Sindy Octafioni; Rofiq Sunaryanto (JURNAL TECHLINK, 2025)
The Cipeucang Landfill receives hundreds of tons of waste daily, mostly organic, and produces gases from anaerobic decomposition, mainly Ammonia (NH₃) and Hydrogen Sulfide (H₂S). This study aims to analyze NH₃ and H₂S concentrations in ambient air around Cipeucang Landfill based on distance (0 m, 100 m, 300 m, 900 m) and time (morning, afternoon, evening). Gas concentrations were measured using the indophenol method for NH₃ and the methylene blue method for H₂S. Meteorological factors including temperature, humidity, and wind speed were also recorded. Results showed that the highest NH₃ concentration was 0.981 ppm measured in the morning at the landfill center, while the highest H₂S concentration was 0.273 ppm. Both gases decreased with distance and varied temporally, with higher levels in the morning and evening. Regression analysis revealed that distance had a strong influence on H₂S concentration, while temperature and humidity had weaker effects. Although concentrations remained below the national ambient air quality standards, the presence of these gases poses potential health and environmental risks. Keywords: Ammonia, Hydrogen Sulfide, Ambient Air, Landfill, Air Pollution